Hsa-mir-499 rs3746444 polymorphism and cancer risk: a meta-analysis - Zou, Peng (Editorial Department of Journal of Biomedical Research, 2012)
MicroRNAs (miRNAs) are gene regulators involved in numerous diseases including cancer, heart disease, neurological disorders, vascular abnormalities and autoimmune conditions. Although hsa-mir-499 rs3746444 polymorphism was shown to contribute to the susceptibility of multiple genes to cancer, the data have yielded conflicting results. Therefore, this meta-analysis was performed to provide a comprehensive assessment of potential association between hsa-mir-499 rs3746444 polymorphism and cancer risk. In this meta-analysis, a total of 9 articles regarding 10 eligible case-control studies in English (including 6134 cases and 7141 controls) were analyzed. No significant association between hsa-mir-499 rs3746444 polymorphism and overall cancer risk was demonstrated. However, an increased risk was observed in the subgroup of breast cancer patients (G allele vs A allele: OR = 1.10, 95% CI = 1.00-1.20; P(heterogeneity) = 0.114; I(2) = 53.9%) and population-based studies (G allele vs A allele: OR = 1.12, 95% CI = 1.00-1.25; P(heterogeneity) = 0.062; I(2) = 64.0%). The findings suggested an association between hsa-mir-499 rs3746444 polymorphism and increased risk to breast cancer.